Histopathological Pattern of Gynecological Malignancies at Tribhuvan University Teaching Hospital, Nepal: A 3 years Study - Bishal Khaniya (Nepalese Medical Journal, 2021)
Introduction: Gynecological malignancies include malignancies affecting the female reproductive organs ovary, cervix, body of uterus, vulva, vagina, and gestational trophoblastic neoplasia.